PENINGKATAN KUALITAS RESTORAN DENGAN PENDEKATAN QUALITY FUNCTION DEPLOYMENT (QFD) (Studi pada Bakso Rusuk Solo) - Permata, Viasti Intan; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2020)
Bakso Rusuk Solo is a restaurant that sells a variety of meatballs with its specialty on the meatballs with ribs. Bakso Rusuk Solo was founded by Sardomo in 2006. This restaurant has four outlets spread across East Jakarta and Bekasi. The food business is a business that is growing rapidly and the growth of its competitors is unbelievable. Besides, the restaurant business also has to think about the service quality, because if the costumers are disappointed it will bring a huge disadvantage to the restaurant. Bakso Rusuk Solo in the last six quarters has experienced a significant decrease in turnover and the increase in the turnover has not been able to cover the decline that occurred. The decrease in turnover can be caused by the quality of services that need to be improved. Service quality improvements are also beneficial for restaurants to be able to know about customer expectations and desires. This research aims to analyze the priority requirements of Bakso Rusuk Solo service quality which are grouped in five quality dimensions of DINESERV measurement (tangibles, assurance, reliability, responsiveness, and empathy). The number of samples in this research was chosen by purposive sampling technique and collected through questionnaire techniques. This research involved 96 respondents who are Bakso Rusuk Solo costumers. This research also involves the assessment of the owner of Bakso Rusuk Solo to strengthen the appraisal of its customers. The priority of customer’s requirements is analyzed using the Importance-Performance Analysis (IPA) method and Quality Function Deployment (QFD). The results of this research are discovered that